2015
DOI: 10.1007/s11325-015-1135-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nondipping pattern on systemic inflammation in obstructive sleep apnea

Abstract: In conclusion, nondipping pattern appears to be associated with increased serum IL-2 levels indicating the increased inflammatory response independently from OSAS severity, and this pattern should be evaluated carefully for possible cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Although the levels of IL-10 have been investigated in OSAS [4,[27][28][29][30][31][32], promoter polymorphisms of IL-10 gene have not been studied before. We found that IL-10-1082 GA, AA, GA-AA, −819 CT-TT, and −592 CA, AA, CA-AA genotypes increased the risk for developing OSAS as well as the severity of OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the levels of IL-10 have been investigated in OSAS [4,[27][28][29][30][31][32], promoter polymorphisms of IL-10 gene have not been studied before. We found that IL-10-1082 GA, AA, GA-AA, −819 CT-TT, and −592 CA, AA, CA-AA genotypes increased the risk for developing OSAS as well as the severity of OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings of higher circulating levels of the inflammatory factor interleukin-2 in OSA patients with a nondipping blood pressure profile also support a role for inflammation in the development of nondipping blood pressure [30].…”
mentioning
confidence: 84%
“…Increase in pro-inflammatory cytokines have been reported in both adult OSA (CRP [19,20], TNF-α, IL-6 [21], and IL-10) and pediatric OSA patients (HS-CRP) [10,11]. In this study, we investigated cytokines in children with both OSA and enlarged adenoids or tonsils and focused on their changes before and after T&A.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our previous finding [11], children with both diagnoses had higher cytokine levels than normal controls (Table 1). Although improvement is always noted, T&A cannot cure all children with OSA [19][20][21][22]. Some children kept having abnormal AHI and cytokine levels after T&A, and the intermittent hypoxia during sleep could still lead to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%